Social Media and Political Participation in the 2024 Elections: Survey on Generation Z Voters of Buddhist Society in Indonesia - Robiyanti, Ria Restina; Tatik Purwaningsih; Joko Setyawan; Abdul Kholik (JOM, 2024)
This study examines the influence of social media exposure on political participation among Generation Z Buddhists in Indonesia during the 2024 elections. Elections serve as a democratic mechanism allowing the populace to make decisions through majority votes. Social media has become a primary tool for political campaigns, especially targeting Generation Z, who are more active on digital platforms than traditional media. This research employs a quantitative method by surveying 400 respondents aged 17–26 using purposive sampling. The independent variable is social media exposure, measured through dimensions such as type, frequency, and duration of media use, while the dependent variable is political participation, both offline and online. Linear regression analysis shows that social media exposure significantly influences political participation (t = 2.779; sig. = 0.006 < 0.05). Instagram and TikTok are the dominant platforms, with peak usage occurring between 7:01 PM and midnight. Offline participation primarily involves discussing political issues, while online participation focuses on consuming political information. The findings reveal that social media exposure accounts for 19% of the variance in political participation, supporting the Stimulus-Response theory. This research underscores the importance of social media in enhancing political awareness among Generation Z and recommends future studies explore additional variables such as psychological and social needs and political knowledge.